“20 Years After…” GFE 2.0: A Theoretical Revision and Empirical Testing of the Concept of “Group-Focused Enmity” Based on Longitudinal Data - Heyder, Aribert; Anstötz, Pascal; Eisentraut, Marcus; Schmidt, Peter (Frontiers in Political Science, 2022)
Conceptually, “group-focused enmity” (GFE, long-term project in Germany, duration: 2002-2011) consists of several different attitudes that constitute a syndrome of group-focused enmi-ty. These attitudes are empirically related to each other and share a common core which is the ideology of inequality. But is GFE really a one-dimensional homogeneous ideology? Over the years there have been considerable doubts about this fundamental assumption. We have two central theoretical argumentations for explicating and revising the concept of GFE. The first is based on the social psychological literature regarding differences between ideologies, attitudes, stereotypes and social prejudices. The second arises from one of the basic conceptual ideas of the GFE project, which states that depending on the respective societies different specific groups become targets of devaluation and discrimination. Therefore, we propose a revised version of the GFE syndrome as a two-dimensional concept: an ideology of inequality (generalized attitudes) and social prejudice (specific attitudes). The measurement models are strictly empirically tested using data from the GFE panel (waves 2006, 2008) as well as the representative GFE-surveys (cross-sections 2003, 2011) conducted in Germany. To test for discriminant and external validity, we have also included social domi-nance orientation (SDO). Additionally, within this framework, the methodological focus of the study is to test for several forms of measurement invariance in the context of higher-order fac-tor models considering the issue of multidimensionality of latent variables. Our empirical results support the idea that GFE is a bi-dimensional concept consisting of an ideology of inequality and social prejudice. Moreover, SDO is demonstrated to be empirically distinct from both dimensions and correlates more strongly with the ideology of inequality in comparison to social prejudice. Additionally, the bi-dimensional GFE conceptualization proves to be at least metric invariant both between and within individuals. The impact of our proposed conceptualization and empirical findings will be discussed in the context of international research on ideologies, attitudes and prejudices. The dealing questions are why different explanatory factors have different effects on prejudicial and ideological atti-tudes and why there are different forms and manifestations of social prejudice in different so-cieties over time.